Relationship Among Physical Literacy, Mental Health, and Resilience in College Students - Ma, Ruisi; Liu, Ting; Raymond Sum, Kim Wai; Gao, Tianyu; Li, Minghui; Choi, Siu Ming; Huang, Yan; Xiang, Wenyi (Frontiers in Psychiatry, 2021)
Objectives: To examine the relationship among physical literacy, mental health, and resilience in college students. Methods: Cross-sectional study. Participants (N = 5265; 46.6% Males) completed perceived physical literacy instrument, mental health continuum short form, and the 12-item child and youth resilience measure. Mediation models were applied to explore the association among three concepts. Results: Physical literacy, resilience and mental health were significantly linked with each other. In mediation model, the direct effect of physical literacy on mental health was .49. The indirect effect of physical literacy on mental health through the mediation of resilience was .97. The mediating effect of resilience accounts for 66.30% of the total effect, indicating the partial mediating effect of resilience in the relationship between physical literacy and mental health. In more detailed models, resilience was found to mediate the relationship between physical literacy and social well-being and psychological well-being, accounting for 61.02% and 56.92% of the total effect, respectively. In addition, resilience acted as full mediator in the relationship between physical literacy and emotional well-being (>100%). These findings suggest that physical literacy increases mental health by improving resilience. Conclusions: This is the first time to connect physical literacy with mind factors. The mediating effect of resilience on the relationship between physical literacy and mental health was found. Our findings support the development of physical literacy in universities as part of a holistic approach to supporting undergraduates’ well-being and mental health. This study provides a new perspective for the development of large-scale interventions in the health of body and mind in college students.